A study of delay sources of construction project in Kuantan area - Tan, Kean Wei (2015)
Delays are general phenomenon because construction projects are considered to be a common national issue in almost every construction project around the world and Malaysia could not an exception. This research study about the delay sources of construction project which located in Kuantan area. The objective of this project is to identify the delay sources in construction project and also to analyze the risks of delay sources for construction project in Kuantan area. This study is conducted to find out the numerical value of Risk Priority Number (RPN) from the data and information gained by the targeted respondents through the survey questionnaires. Through RPN, we can identify that most important problem(s) and gives a model to allocate the limited resource in order to minimize the effect on project by delay. The findings of research could increase the awareness and contribute to the construction industry especially in Kuantan area. The identified risk of delay sources are categorized to delay factors related to contractor, consultant, owner and external factors. The findings indicate that the risk of delay sources that related to contractor should be emphasized and focus to minimize the occurrence of delay incident in construction project. To address this issue, the project team should conduct proper risk management to ensure that the progress of project is smoothly. All the result are obtained by performing analysis by SPSS version 2.0 and Microsoft Excel 2012, all the data is been recorded in this research.